ANALISIS EFISIENSI PEMASARAN KOPI ARABIKA DI KOTA SUNGAI PENUH PROVINSI JAMBI - Baviga, Rado; Hamid, Ernawati; Murdy, Saad (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
This study aims to describe the marketing of arabica coffee, analysis farmer’s share and analyze the efficiency of arabica coffee marketing channels. The data used are primary data through direct interviews with farmers to be used as samples and secondary data obtained indirectly such as books that are relevant to the topic under study Arabica coffee farmers samples were determined with random sampling while the sample of traders is determined with snowball sampling. The method of analysis in this research is descriptive analysis by tracing arabica coffee distribution activities from farmers to end consumers. analyzing farmer share marketing functions can be known based on the main activities carried out by each marketing agency. Marketing analysis by calculating marketing margins and farmer’s share, by understanding the differences in costs between institutions and functions performed by each marketing institution. Quantitative analysis answers marketing efficiency by looking at and measuring indicators of marketing efficiency. Marketing efficiency can be seen by using quantitative analysis by looking at several indicators of profit and cost ratio analysis. The results showed that marketing institutions consisted of large traders/industry, cooperative, UKM/industry and traders thinner. There are five marketing channel patterns is I (farmer, large traders/industry, consumer), II (farmer, large traders/industry, UKM/industry, consumer), III (farmer, large traders/industry, UKM/industry, traders thinner, consumer), IV (farmer, cooperative/industry, UKM/industry, consumer), V (farmer, cooperative/ industry, UKM/industry, traders thinner, consumer). Score farmer’s share the highest is in the four channels pattern 27% shows the price received by yhe end consumer close to the price received by the farmer due to the short channel and low operational and processing costs. The last indicator is the profit and cost ratio with the highest 7.3 value from other channels, the highest value indicates that channel four will get high profits and low marketing costs.